Ethical Dilemma of Occupational Duties in Journalism - Nadia Khairina (Yayasan Literasi Sains Indonesia, 2026)
This research aims to explore the conditions of ethical dilemmas in mass media journalists during the 2024 General Election. This study uses a qualitative research design with a phenomenological approach using interview techniques. There were 3 participants. The results of the interview will be analyzed using descriptive analysis techniques. From the results of the study, it is known that the ethical dilemma felt by the participants, indirectly and unconsciously by the participants, was actually seen during the interview. Although participants always remember and hold the principle of remaining neutral, objective and always writing news accurately while carrying out their duties as Journalists, as citizens, participants are still aware of their rights and also their role during the election to continue to vote in support of the candidate pair they support. This tends to cause a feeling of dilemma to choose between 2 situations, namely the tendency to support certain candidates or maintain the integrity of the profession as journalism while covering the 2024 election. However, it is also known that participants do uphold the principles, values, individual rights, and individual obligations as journalists in writing news accurately and objectively. Thus, it can be said that the participants are aware of the ethical elements of a journalist, which causes control/control over the behavior of the participants while carrying out their duties as journalists.